PENGEMBANGAN MODAL INTELEKTUAL DALAM UPAYA PEMBERDAYAAN KELOMPOK DOSEN - Suryadi - Poerbo; Budi - Prasetya; Josef Bambang Trijoga; Jumi - Jumi; Karnowahadi - Karnowahadi (Politeknik Negeri Semarang, 2016)
The objective of this research was to defineintelectual capital develpment model inempowering teacher’s specialities group/KBK at Business Administration Departmentin relation with achievement of its competitiveadvantage. The research variables were:human capital, organizational capital, andrelational capital. The analysis intrumentswere: descriptive analysis and performanceimportanceanalysis. It was found that : therewere some aspects of intelectual capital thatshould be highly developed. they are:leadership, cohecssion, learning andexpenriment.